Scaling of strained-Si n-MOSFETs into the ballistic regime and associated anisotropic effects. - Bufler, F.M.
The dependence of the strain-induced on-current improvement in n-MOSFETs on scaling and the crystallographic orientation of the channel is investigated by self-consistent full-band Monte Carlo simulation. For a channel orientation along the <110> direction, the enhancement decreases weakly from almost 40% to 30% as the effective gate length is reduced from 75 to 25 nm. For the <100> direction, the improvement is about 10% higher. The anisotropy of the drain current, which vanishes for small drain voltages, is attributed to the different band curvatures above 100 meV. This feature appears to be crucial for quasi-ballistic transport of the electrons in the high longitudinal field as they enter the source-side of the channel.
Keywords: 25 to 75 nm; Si; Anisotropic effects; Ballistic regime; Channel crystallographic orientation; Full-band Monte Carlo simulation; High longitudinal field; Quasi-ballistic transport; Self-consistent Monte Carlo simulation; Strain-induced on-current improvement; Strained-Si n-MOSFETs.; Velocity overshoot